Trace level voltammetric determination of Zn(II) in selected nutrition related samples by bismuth-oxychloride-multiwalled carbon nanotube composite based electrode - Petrovic, Sandra; Guzsvany, Valeria; Rankovic, Nikola; Beljin, Jelena; Roncevic, Srdan; Dalmacija, Bozo; Ashrafi, Amir M.; Konya, Zoltan; Švancara, Ivan; Vytřas, Karel (Elsevier Science BV, 2019)
Bismuth-oxychloride-multiwalled carbon nanotube composite material was applied as surface modifier of glassy carbon electrode (BiOCl-MWCNT/GCE) for rapid and reliable trace level determination of Zn(II) in selected foodstuffs. The method development encompasses the optimization of electrode preparation including the transmission electron microscopic study of the modifier suspension, selection of the supporting electrolyte pH, the adjustment of the operation parameters of the SW-ASV measurements and the investigation of matrix effects. By the BiOCl-MWCNT/GCE recorded calibration curve showed an excellent linearity towards Zn reoxidation peak intensity in the concentration range from 2.50 to 80.0 mu g L-1 with the calculated LOD of 0.75 mu g L-1 which was associated with 120 s accumulation time and accumulation potential -1.40 V vs SCE in acetate buffer pH 4.5. A satisfactory repeatability expressed as relative standard deviation of 4.8% was obtained in the case of 10.0 mu g L-1 Zn(II) in model solution. The Zn(II) reoxidation signal from BiOCl-MWCNT/GCE received by the optimized SW-ASV method was compared with those recorded with bare, classical bismuth-film, multiwalled carbon nanotubes and by in situ made advanced bismuth-film-MWCNTs working electrodes. The applicability of the proposed BiOCl-MWCNT/GCE based method was corroborated via measuring the target analyte in two nutrition related real samples: in a dietary supplement and in a brewer's yeast sample. Comparative flame atomic absorption spectrometric measurements verified the obtained results in the case of yeast sample.
Voltametrické stanovení Zn(II) na stopové úrovni ve zvolených vzorcích doplňků stravy pomocí uhlíkové kompozitní elektrody na bázi uhlíkových nanotrubic a chloridu bismuthylu
Keywords: BiOCl-MWCNT/GCE; SW-ASV; Trace level determination of Zn(II); Dietary supplement; brewer's yeast; BiOCl-MWCNT/GCE; SW-ASV; stanovení Zn(II) na stopové úrovni; doplněk stravy; pekařské kvasnice